Optimasi Tungku Sekam Skala Industri Kecil Dengan Sistem Boiler - Nawafi, F; Puspita, D; Desna, Desna; Irzaman, Irzaman (BERKALA FISIKA, 2010)
Rice husk furnaceÂ is a technology based on local wisdom to anticipate threats crisis energy. At first investigated husk stoves for cooking only in the scale of the household, but today rice husk furnace developed for industrial scale because of the importance of commercial aspects of a very promising from this rice husk furnace. In rice husk furnace also developed an industrial scale boiler system, boiler systems where it can enlarge its efficiency, in the midst of a boiler chimney pots have used, because basically rice husk furnace process is influenced by air flow. Husk furnace efficiency greatly affect the number of furnace ash which is required in the cooking process. Â Keywords: rice husk, rice husk furnaces, air flow, efficiency, boilers.